HUBUNGAN KELAINAN REFRAKSI DENGAN PRESTASI AKADEMIK SISWA SMA MUHAMMADIYAH 3 YOGYAKARTA - AT Titis Ayu Wulandari (2013)
Myopia is a refractive disorder with high prevalence in Indonesia and is found in school-age children. Myopia is influenced by heredity, gender, and environmental factors such as length and distance of reading. The purpose of this study was to determine the proportion of students suffering from myopia and those who did not suffer from myopia. And to analyze the correlation between myopia and students academic achievement at SMA Muhammadiyah 3 Yogyakarta. This was an observational - Cross Sectional Study. The population was students of grade XI IPA and XI IPS who met the inclusion and exclusion criteria. Seventy eigh (35,8%) students suffer from myopia and 140 (64,2%) students did not. Of 78 students suffering from myopia, 67 (85,9%) had good academic achievement while the rest (14,1% of 11 Students) had poor academic achievement. Ninenty- One (65,0%) of 140 students who did not suffer from myopia, on the other hand, had good academic achievement, while the rest (35,0% or 49 students) showed poor academic achievement. Data analysis using Chi-Square Test revealed a significant value of 0,001 (P<0,05%), with OR=0,305, which exhibited that myopia students had good academic achievement.